PHILOKALIA IN MUSIC - COROIU , Petruţa-Maria (Studia Universitatis Babes-Bolyai Musica, 2012)
I thought a view on music history based on the 30 stages of The Ladder written by Sf. John, exposing the most important musical masterpieces, associated with spiritual values. Through a good spiritual education, through musical values we can achieve the ideal of the true music (not merely aesthetic): the good taste, the authentic feelings, beliefs and attitudes. The ladder of the virtues (Philokalia volume. IX) is one of the most representative and important writings of the Orthodoxy.